Taurine alleviates oxidative stress in porcine mammary epithelial cells by stimulating the Nrf2‐MAPK signaling pathway. Issue 4 (22nd January 2023) - Xu, Mengmeng; Che, Long; Gao, Kaiguo; Wang, Li; Yang, Xuefen; Wen, Xiaolu; Li, Mengyun; Jiang, Zongyong
Abstract: The high incidence of oxidative stress in sows during late gestation and lactation affects mammary gland health, milk yield, and milk quality. Recently, we found that supplementing maternal diets with 1% taurine improved antioxidant capability and enhanced growth performance in offspring; however, the mechanisms underlying these are unknown. This study aimed to investigate the cytoprotective effects and the mechanism of taurine in mitigating oxidative stress in porcine mammary epithelial cells (PMECs). PMECs were pretreated with 0–2.0 mM taurine for 12 h and then subjected to oxidative injury with 500 μM hydrogen peroxide (H2 O2 ). Pretreatment with taurine attenuated decreased cell viability, enhanced superoxide dismutase, and reduced the intracellular reactive oxygen species accumulation after H2 O2 exposure. Taurine also prevented H2 O2 ‐induced endoplasmic reticulum stress. Nuclear factor erythroid 2‐related factor 2 (Nrf2) was essential to the cytoprotective effects of taurine on PMECs, as Nrf2 knockdown significantly inhibited taurine‐induced cytoprotection against oxidative stress. Moreover, we confirmed that Nrf2 induction by taurine was mediated through the inactivation of the p38/MAPK pathway. Overall, taurine supplementation has beneficial effects on redox balance regulation and may protect against oxidative stress in lactating animals. Abstract : Taurine prevented H2 O2 ‐induced cell apoptosis. Taurine prevented H2 O2 ‐induced endoplasmic reticulum stress. Taurine supplementation may protect against oxidative stress in lactating animals.